Ideological and stylistic dominants of the artistic world of Arnosht Lustig - Vostrykava, Alena U. (Journal of the Belarusian State University. Philology, 2021)
Arnosht Lustig is one of the most famous Czech writers of the second half of the 20th – early 21st centuries, who wrote about the World War II. His place in Czech military prose is determined by the fact that he is a monothematic author, since he wrote exclusively on the topic of the holocaust, and himself, being a Jew, went through concentration camps. The article examines the ideological and stylistic dominants of the writer’s work, characterises his place and role in the Czech literature. The author of the study considers it very important to introduce A. Lustig’s work into the Belarusian literary and cultural life, since the theme of war and the tragic fate of the people belongs to a large literary segment both in Belarusian and Russian literature, as well as in the literature of other Slavic peoples of Europe. Since A. Lustig emigrated from Soviet Czechoslovakia, his books were not mentioned in his homeland and were not known in the Soviet Union. We consider it necessary to fill the existing cultural gaps. We emphasise that the military prose of the Czech author was very different from the official Czech literature, which appealed to military realities and was distinguished by heroic pathos, communist ideology, while A. Lustig wrote about the sufferings of Czech Jews, mainly young girls, children, old people, through the prism of an existential vision of the world. His books are characterised by drama, psychological approach to the interpretation of the military theme and presentation of images. The writer focuses exclusively on ethical issues, avoiding unambiguous approaches to artistic material and black-and-white palette when portraying the characters in his works. We highlight such important themes in A. Lustig’s prose as the theme of revenge and lost love, the awakening of human consciousness and human solidarity. Specific examples of their embodiment in the stories and novels of the Czech author are given. We analyse the features of A. Lustig’s style, which are the presence of several time plans, the importance of leitmotif details.
Keywords: Czech literature; Arnosht Lustig; military prose; holocaust theme; psychologism; ethical issues; drama; revenge theme; lost love theme; human solidarity theme; consciousness awakening theme; artistic style